One earth, one future : our changing global environment - Silver, Cheryl Simon (National Academy Press, 1990)
Explains the problems that threatens our planet's environmental systems.
Keywords: Nature -- Effect of human beings on.; Pollution.; Global warming.; Environmental policy.; Environmental Pollution; Global Warming; Êtres humains -- Influence sur la nature.; Réchauffement de la Terre.; Environnement -- Politique gouvernementale.; global warming.; environmental policy.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy.; Environmental policy; Global warming; Nature -- Effect of human beings on; Pollution; Mensch; Umweltveränderung; Umweltverschmutzung; Umweltbewusstsein; Aufsatzsammlung; Politique de l'environnement.; Nature -- Effets de l'homme.; Environmental degradation.; Air pollution.